Electronic structure modification of polymeric PEDOT:PSS electrodes using the nonionic surfactant Brij C10 additive for significant sheet resistance reduction - Choi, Seungsun; Kim, Wonsik; Shin, Woojin; Han, Hye Ji; Park, Chaeryeon; Oh, Hyesung; Jung, Sehyun; Park, Soohyung; Lee, Hyunbok (Elsevier BV, 2023)
The development of efficient transparent conducting electrodes (TCEs) is of great importance for achieving high-performance optoelectronic devices. Poly(3,4-ethylenedioxythiophene)-poly(styrene sulfonate) (PEDOT:PSS) is a well-known conducting polymer used in a wide range of applications. However, for electrode applications, the sheet resistance (Rsheet) of PEDOT:PSS must be significantly reduced to replace conventional TCEs. In this study, we demonstrated a significant decrease in Rsheet of a PEDOT:PSS film by mixing polyethylene glycol hexadecyl ether (Brij C10) into the PEDOT:PSS solution. The electronic structure modified by the rearrangement of con-ducting PEDOT and insulating PSS with Brij C10 was investigated using X-ray photoelectron spectroscopy. The Brij C10 additive altered the interaction between PEDOT and PSS, and the relative ratio of conducting PEDOT on the film surface increased, thereby facilitating efficient charge transport. Using the reduced Rsheet, perovskite solar cells (PSCs) with a Brij C10-modified PEDOT:PSS anode were fabricated. The power conversion efficiency of the PSCs was remarkably improved by reducing Rsheet, indicating the high potential of the PEDOT:PSS electrode.